Una finestra sulla psichiatria tedesca. Qualcosa di nuovo sul fronte del Male? Breve florilegio mitologico - Strasser, Peter (Il sogno della farfalla, 2012)
Even if we live in an era that believes in science, in some areas that closely affect our sensibility we are able to find regurgitations of archaic thinking. The essay deals in particular with two popular explanations of the phenomenon of “Evil”. The first explanation assumes that there are individuals who are evil by nature. This belief is a re-edition of the Homo delinquens, described by C. Lombroso as a beast under the semblance of a “sick-evil” person. The second explanation points to the idea of a “beast in all of us”: we are all born criminals, even though there is what we could call a homeopathic dilution in each individual. The article shows how both explanations are clear examples of a pseudoscientific attitude.